Mitigating seasonality in tourism by attracting young travellers: evidence from Cyprus - Liasidou, Sotiroula; Berjozkina, Galina; Pipyros, Kosmas (My University, 2022)
Purpose – Generation Z, Millennials, young travellers or iGeneration represent the age range from 18 to 29 with uniquely different characteristics and tourism preferences. This study aims to understand the travel behaviour of young travellers in terms of the travel decisions they make and their involvement in tourism activity. Design/methodology/approach – Primary data collection was facilitated by a focus group discussion with 12 participants from this age group. Findings – Study results suggest that young travellers are attracted to technologically advanced destinations that provide multi-purpose experiences. Competitive tourism destinations are those adjusted to the needs of this cohort of travellers’ propensity to embrace change and innovation. Considering the needs and expectations of young travellers is key to a destination’s long-term survival and sustainability, as the market share of young travellers is rapidly growing. Originality/value – The study looks at the trends in this emerging market segment and discusses new generational behaviour. Furthermore, the study provides insight into ways to make destinations attractive as year-round experiences and thereby control the problem of seasonality.
Keywords: Young travellers; Millennials; Seasonality; Seasonality; Cyprus; Focus group